An introduction to radar image processing in ecology - Stepanian, Phillip M.; Chilson, Phillip B.; Kelly, Jeffrey F.; Tatem, Andrew (Methods in ecology and evolution, 2014)
Summary Use of radar in ornithology, chiropterology and entomology continues to increase, driven in part by widespread online data availability. In addition to research applications, rapid growth in areas such as wind energy and aviation has prompted the use of radar for conservation. While a variety of research applications motivate ecologists to gain basic radar literacy, the ability to process and analyse radar data sets can be a daunting task that may dissuade inexperienced ecological radar users. This effect is exacerbated by vague radar methodologies in the ecology literature, as well as the combination of complex techniques and unfamiliar terminology in other radar‐focused disciplines. While radar data come in many formats and levels of detail, a common type is the two‐dimensional radar image. As rasters of data with associated spatial coordinates, radar images are relatively easy to manipulate, especially for those familiar with basic raster computations. Furthermore, because radar image data require relatively small storage space, they can be readily downloaded from a number of online sources. With this in mind, radar images provide a convenient foundation for ecological applications. A primer on radar image interpretation and processing is presented, with a focus on image composition for typical atmospheric surveillance radar scans. Additionally, a selection of existing ecological radar image processing methods are overviewed. As a starting point, a basic algorithm for automated image processing is outlined that may be modified to create specialized workflows. Three examples of the application of this algorithm are included, illustrating its modification and use for automated feature extraction. By outlining a basic algorithm, we hope to provide a clear starting point for the beginning radar user. When combined with additional existing methods, this algorithm provides a wide range of refinements and modifications that can pave a path towards sophisticated radar processing workflows. In the long term, the ability of ecologists to independently analyse radar data will lead to better ecological interpretation of radar data and a more informed application to conservation policy. Video